GERAKAN RUMAH SEHAT : KAMPANYE LINGKUNGAN BERSIH BEBAS DEMAM BERDARAH DENGUE (DBD) DI DESA SIONGGANG KECAMATAN BUNTU PANE TAHUN 2025 - Munthe, Seri Asnawati; Liarosa Veronika Sinaga; Jasmen Manurung; K, Yuni (Universitas Sari Mutiara Indonesia, 2025)
Dengue Hemorrhagic Fever (DHF) is one of the environmental-based diseases, namely a pathological condition in the form of abnormal function or morphology of an organ of the body caused by human interaction with everything around it that has the potential for disease. The environment greatly influences the incidence of Dengue Hemorrhagic Fever (DHF), especially an environmental condition with poor sanitation (Arsyad et al., 2020).. Dengue Hemorrhagic Fever (DHF). For this reason, a clean house movement is needed to eradicate mosquito breeding places. This Community Service aims to increase public awareness of mosquito breeding places and reduce DHF cases. After participating in the Healthy Home Movement, it turned out that the community was enthusiastic about participating and there was an increase in knowledge from an average of 56 before and an average after counseling of 88 so that there was an increase of 32 points. In addition, the mutual cooperation participants were also very enthusiastic, as seen from various parties involved and even the village head provided the necessary equipment. For this reason, it is hoped that the community will be able to prevent the spread of Dengue Fever so that DHF cases decrease and the home environment is clean.